The effect of hearing aid microphone mode on performance in an auditory orienting task - Brimijoin, W. Owen; Whitmer, William M.; McShefferty, David; Akeroyd, Michael A. (Lippincott, Williams & Wilkins, 2014)
OBJECTIVES: